2020
DOI: 10.1155/2020/9761539
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caveolin-1 in Diabetes and Its Complications

Abstract: It is estimated that in 2017 there were 451 million people with diabetes worldwide. These figures are expected to increase to 693 million by 2045; thus, innovative preventative programs and treatments are a necessity to fight this escalating pandemic disorder. Caveolin-1 (CAV1), an integral membrane protein, is the principal component of caveolae in membranes and is involved in multiple cellular functions such as endocytosis, cholesterol homeostasis, signal transduction, and mechanoprotection. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 227 publications
(231 reference statements)
5
70
1
Order By: Relevance
“…Both the lower fat mass ( 32 ) and the increased lean mass ( 28 ) are consistent with prior reports in mice and with the known association with lipodystrophy in human patients ( 4 ). The poor insulin sensitivity and the oral glucose tolerance AUCs are also consistent with earlier reports ( 33 , 34 ). The previous publication showing that Cav1 knockout mice had difficulty with the forced swim test ( 27 ) makes sense because of their reduced ability to rapidly internalize glucose; the present study is the first to show that this is true even for a routine activity—in homozygous and, to a lesser extent, in heterozygous animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both the lower fat mass ( 32 ) and the increased lean mass ( 28 ) are consistent with prior reports in mice and with the known association with lipodystrophy in human patients ( 4 ). The poor insulin sensitivity and the oral glucose tolerance AUCs are also consistent with earlier reports ( 33 , 34 ). The previous publication showing that Cav1 knockout mice had difficulty with the forced swim test ( 27 ) makes sense because of their reduced ability to rapidly internalize glucose; the present study is the first to show that this is true even for a routine activity—in homozygous and, to a lesser extent, in heterozygous animals.…”
Section: Discussionsupporting
confidence: 92%
“…The data shown are from regular chow-fed animals; OGTT was not possible in HFD + STZ mice because their glucose readings were higher than the measurable level throughout the first 90 min of the OGTT test, regardless of genotype. This lower insulin sensitivity is consistent with earlier studies on caveolin 1, which directly regulates insulin receptors (33,34).…”
Section: Cav1 P158pfsx22 Homozygous Mice Have Altered Body Compositiosupporting
confidence: 92%
“…A further question is whether the synaptic function of Cav1 related to a neural disorder. Studies have revealed that Cav1 or lipid rafts are implicated in neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) [ 18 20 ], and that Cav1 is also involved in non-neural diseases such as cancer and diabetes [ 21 , 22 ]. The remaining questions are challenging, but emerging high-resolution imaging (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that Cav-1 polymorphisms increase MetS risk through altered Cav-1 gene expression, attenuating dyslipidemia and hypertension, while impairing glucose and insulin homeostasis [12][13][14]20 . Cav-1 regulates signaling molecules, such as IRS1, that have a key role in appropriate insulin responses, PKA, angiotensin II receptors, active blood pressure molecules, and binding sites for calcium ions; all of these may affect various clinical traits of MetS 14,21,22 . Additionally, Cav-1 is able to effect NO, insulin, lipids, and hormone metabolisms 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms are unclear, but it seems that Cav-1 is able to regulate several key enzymes in lipid metabolism, such as cholesterol ester transfer protein and phospholipid transfer protein 13 . While the association between Cav-1 polymorphisms and type 2 diabetes risk has been widely reported in various populations 14 , these relationships with MetS have been inconsistent, despite several publications on the association between Cav-1 gene variants and serum lipid pro les [14][15][16][17] . To the authors' knowledge, there has been no study evaluating Cav-1 rs3807992 variant, metabolic risk factor, and the interaction of fatty acid intake levels with this SNP.…”
Section: Introductionmentioning
confidence: 99%